Materialism Gospel among Pentecostal Christians of Cameroon: A Sociological Study - Mendong, Margaret B.-M. (International Scholar Journal of Arts and Social Science Research, 2023)
This research aims to explain materialism gospel and its impact on the lives of Christians in Cameroon. The mixed research method was used in this study. Questionnaires, interviews and participant observation were the main methods used to obtain primary data. Results from this research show that attractive messages were used to entice people to adhere to materialism gospel. Economic hardships, freedom of worship, among other appealing messages were exploited to lure people to believe in this doctrine. Christians believed that they had to pay tithes, give offerings, avoid sins and pray without ceasing to provoke God to bless them with material wealth. Christians invested in economic activities as they were sure to make profits thanks to God’s blessings. Unfortunately, many materialism gospel Christians became lazy and poor as they believe that the payment of tithes, prayers and church offerings would give abundant material blessings; blessings many are still waiting for.
free
Keywords: Academic; Arts; International; Journal; Peer; Publication; Research; Review; Scholarly; Science; Social; scholars